Peran Pertanian Organik Terhadap Kesejahteraan Petani di Kecamatan Sumbersari Kabupaten Jember - Sari, Cantika Puspita; Putri, Nur Aniza Cahyaning; Widhah, Cindy Padma; Pangestu, Dhandy; Suaysyah, Sri; Prabowo, Rachmat Udhi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Organic farming is an agricultural practice that prioritizes the use of natural ingredients and environmentally friendly techniques in producing food. Organic farming practices place greater emphasis on maintaining ecosystem balance, soil health and environmental sustainability. The organic farming program implemented by the Jember Regency government in its application is carried out through empowering farming communities. This research was conducted in Sumbersari District, Jember Regency, precisely in Karangrejo Village using qualitative analysis methods and a snowball sampling approach. Sampling is initially small, then increases over time and stops when the information obtained is deemed sufficient. The aim of this research is to find out the role of organic farming in the welfare of farmers in Sumbersari District, Jember Regency. Based on interviews and observations, the results showed that organic farming implemented by farmers in Sumbersari District was still unable to improve farmers' welfare, which was not in accordance with the theory that organic farming should be able to help improve farmers' welfare because the price of organic products was higher than non-organic products. One of the reasons for the low income of organic farmers in Sumbersari District is because farmers do not have organic certification so their products are not priced according to the price of organic products. Decreased productivity and inappropriate prices are factors that cause a decline in the welfare of organic farmers in Sumbersari District, Jember Regency.